Innovation Development of Coffee Berry Borrer (Hypothenemus hampei Ferr.) Pest Control Technology and Their Effectiveness - Siska Rasiska (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2021)
The Coffee Berry Borer (CBB) (Hypothenemus hampei Ferrari)(Coleoptera:Curculionidae:Scolytinae) is a major pest of coffee plants. It caused damage to coffee berries and economic losses for farmers. Various technologies have been carried out to control CBB, including cultural biological, chemical, and sanitation. However, of the technology control of CBB, only a few literature that discussed the effectiveness and efficiency, both socially, economically and their impact on the environment. Thus, this paper aimed to: 1) review research CBB control technology based on characteristics; and 2) assessing the effectiveness and efficiency of the technology in controlling CBB based on compatibility, applicability, availability, safety, sustainability, affordability and economic. This study was conducted using a systematic review of the literature from the search engine Science.direct, Google.scholar, which was identified from 1996 to 2020. The search resulted showed that there were 59 articles related to CBB control technology and were divided into several types, namely 22 articles that discuss technology in cultural, 31 articles that discuss biological control, 5 articles that discuss technology chemically, and 1 articles that discusses orchard sanitation technology. CBB control technologies that are considered to have compatibility, safety, sustainability, affordability and economic are cultural, biological control and sanitation. However, if it is related to applicability and availability, cultural and sanitation can be the main choice. Many studies on biological technology showing advantages compared to other technologies, thus, biological control technology as a preventive and monitoring effort is still being developed. One of them is developing biological technology with a landscape approach.